STRATEGI DAKWAH RASULULLAH SAW DALAM MEMBANGUN MASYARAKAT ISLAM DI MAKKAH DAN MADINAH - Naura, Nabila; Fitriyanti, Yuli; Roitona Nasution, Rusdiah; Nurzena (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
The da'wah carried out by the Prophet Muhammad served as an important foundation for the formation of a civilized Islamic society. This paper discusses the da'wah strategies implemented by the Prophet Muhammad during two significant periods, namely Mecca and Medina, as well as their impact on social change. The approach used in this study is a literature review, examining various relevant sources. Based on the analysis, the da'wah strategy in Mecca emphasized strengthening faith and patience in facing rejection, while in Medina it focused more on the establishment of social, political, and legal systems. These differences in approach demonstrate the Prophet Muhammad’s ability to adapt da'wah strategies to the conditions of society. Therefore, these strategies remain relevant in modern life, particularly in building a harmonious society based on Islamic values.